The length of a short sperm: Elongation and shortening during spermiogenesis in Cotesia congregata (Hymenoptera, Braconidae). Issue 2 (March 2017) - Uzbekov, Rustem; Burlaud-Gaillard, Julien; Garanina, Anastasiia S.; Bressac, Christophe
Abstract: The spermatozoon of the parasitoid wasp Cotesia congregata is an extremely short gamete measuring less than 7 μm; it is as yet the shortest flagellated sperm to be identified. The mature sperm consists of an acrosome, surrounded by an extra cellular coat, a condensed nucleus, two uncoiled mitochondrial derivatives and a short axoneme. Testes of young adults contain a continuum of differentiation stages. Initially, the flagellum is approximately 5 μm long. It conserves its length in round, elongated and mature spermatids, but is reduced to less than 3 μm in mature spermatozoa. The nucleus is 2 μm in diameter when round, 10 μm long when it becomes a long boat-hull shaped filament, and then reduces to 3.6 μm. Thus, during development the gamete reaches a total length of 15 μm before finally reducing to less than half that length. Some traits of mature sperm anatomy are similar to related species of the Braconidae family, but others seem to be specific and could be due to the shortness of the cell. This uncommon elongation and subsequent shortening of such a tiny flagellated cell constitutes a model for both nucleus and cilium development. Graphical abstract: Highlights: Cotesia congregata has a flagellated sperm less than 7 μm long, it is as yet the shortest sperm in animals. Mature sperm are conform to Hymenoptera but show some peculiarities. Spermiogenesis is continuous in testis of young adult males. In the course of differentiation, both nucleus and flagellum grow longer than in mature sperm. Spermatid shortening has not been described in other species.